2010
DOI: 10.1038/jcbfm.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Arterial Responses to Hypercapnia and Visual Stimulation

Abstract: Despite the different origins of cerebrovascular activity induced by neurogenic and nonneurogenic conditions, a standard assumption in functional studies is that the consequence on the vascular system will be mechanically similar. Using a recently developed arterial spin labeling method, we examined arterial blood volume, arterial-microvascular transit time, and cerebral blood flow (CBF) in the gray matter and in areas with large arterial vessels under hypercapnia, visual stimulation, and a combination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…The hemodynamic parameters measured with MRF‐ASL were in general agreement with previous literature and are within the expected range. Similarly, our observations of an increased CBF (by approximately 58%) and a decreased BAT (by approximately 14%) during CO 2 inhalation are in good agreement with reports of Ho et al and Donahue et al . Overall, we found that the hemodynamic parameters estimated are reproducible across runs, with a COV of CBF and BAT being 9.6 and 3.6%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The hemodynamic parameters measured with MRF‐ASL were in general agreement with previous literature and are within the expected range. Similarly, our observations of an increased CBF (by approximately 58%) and a decreased BAT (by approximately 14%) during CO 2 inhalation are in good agreement with reports of Ho et al and Donahue et al . Overall, we found that the hemodynamic parameters estimated are reproducible across runs, with a COV of CBF and BAT being 9.6 and 3.6%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Although the sequence parameters were different from the one used in the hypertension study, the resultant optimal strength is expected to be independent of the sequence parameters because all the dataset was eventually compared against the highest b value dataset acquired with the same sequence. The optimized b value of 3 s/mm 2 in our study is similar to the b values used in previous human studies ( b = 1.8–4.5 s/mm 2 ) . Even though different crushing gradient strengths have different cutoff velocities, the separation of different arterial segments by the crushing gradients was not feasible.…”
Section: Discussionsupporting
confidence: 73%
“…Further study using methods such as phase-contrast flow quantification is clearly warranted. Another promising avenue of investigation is the use of pulsed or continuous ASL methods with variable delay times (31), which allow measurement of the tag inflow curve and, by fitting with kinetic models, quantitative estimation of CBF. These may help refining and validating single-subtraction versions of ASL techniques.…”
Section: Discussionmentioning
confidence: 99%